2016
DOI: 10.1007/s13361-016-1401-5
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Temperature Effects in the Argon Cluster Ion Sputter Depth Profiling of Organic Materials Using Secondary Ion Mass Spectrometry

Abstract: Abstract. A study is presented of the effects of sample temperature on the sputter depth profiling of two organic materials, NPB (N,N′-Di(1-naphthyl)-N,N′-diphenyl-(1,1′-biphenyl)-4,4′-diamine) and Irganox 1010, using a 5 keV Ar 2000 + cluster ion beam and analysis by secondary ion mass spectrometry. It is shown that at low temperatures, the yields increase slowly with temperature in accordance with the Universal Sputtering Yield equation where the energy term is now modified by Trouton's rule. This occurs up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
(65 reference statements)
1
11
0
Order By: Relevance
“…Similar results have been observed for the cluster ion beam C 60 + for the depth profiling of poly(methylmethacrylate) . Recent experiments by Seah and coworkers using Ar GCIB sputtering of molecular layers have shown that both the depth resolution and the SIMS spectra are very dependent on the sample temperature. The depth resolution decreased and then increased with sample temperature as the diffusion regime changed from surface diffusion to bulk diffusion.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Similar results have been observed for the cluster ion beam C 60 + for the depth profiling of poly(methylmethacrylate) . Recent experiments by Seah and coworkers using Ar GCIB sputtering of molecular layers have shown that both the depth resolution and the SIMS spectra are very dependent on the sample temperature. The depth resolution decreased and then increased with sample temperature as the diffusion regime changed from surface diffusion to bulk diffusion.…”
Section: Resultssupporting
confidence: 79%
“…This was attributed to an increase in sputter rate with temperature. Increases in sputter rates with increasing sample temperatures are observed for a wide variety of materials, including metals, using both atomic and cluster beams …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that the peak was more affected by the beam energy than the centroid and attributed this to the changes in sputtering rate during the initial transient effect at the surface. At depths beyond the initial transient, the centroid of delta functions can mark positions extremely accurately and Seah et al [ 8 ] show data for organic materials in this way with very low scatters of 0.4 nm in depth over 250 nm. An example of the rate change in the outermost 5 nm of organic material is given by Seah et al [ 9 ] who point out the need to consider whether the interface is blurred locally (so that the composition changes slowly) or if it is sharp locally and blurred by the summing of separate events over the wavy surface.…”
Section: Introductionmentioning
confidence: 99%